The 2nd Baltic Osseointegration Academy and Lithuanian University of Health Sciences Consensus Conference 2019. Summary and Consensus Statements: Group I - Biological Aspects of Tooth Extraction, Socket Healing and Indications for Socket Preservation - Gintaras Juodzbalys; Povilas Daugela; Onurcem Duruel; Maria Helena Fernandes; Pedro de Sousa Gomes; Samir Goyushov; Lorena Mariano; Lukas Poskevicius; Arturas Stumbras; Tolga Fikret Tözüm (Stilus Optimus, 2019)
Introduction: The task of Group I was to review and update the existing data concerning the physiologic process of socket healing, in the absence or presence of grafting materials or platelet concentrates, addressing the associated molecular and cellular events that culminate in the restoration of the lost tissue architecture and functionality. The second task was to review current literature concerning extraction socket classification immediately following tooth extraction and the rationales for socket preservation/augmentation procedures and with reference to it suggest novel clinical decision tree for extraction socket preservation/augmentation in aesthetic and non-aesthetic area. Material and Methods: The main areas indicated by this group were as follows: socket healing process, including haemostasis and coagulation, inflammatory phase, proliferative phase, bone tissue modelling and remodelling; socket healing with graft materials and autologous platelet concentrates; extraction socket classifications; indications and reasons for extraction socket preservation/augmentation. The systematic reviews and/or meta-analyses were registered in PROSPERO, an international prospective register of systematic reviews: http://www.crd.york.ac.uk/PROSPERO/. The literature in the corresponding areas of interest was screened and reported following the PRISMA (Preferred Reporting Item for Systematic Review and Meta-Analysis) Statement: http://www.prisma-statement.org/. Method of preparation of the systematic reviews, based on comprehensive search strategies, was discussed and standardized. The summary of the materials and methods employed by the authors in preparing the systematic reviews and/or meta-analyses is presented in Preface chapter. Results: The results and conclusions of the review process are presented in the respective papers. One theoretical review-analysis and one systematic review were performed. The group's general commentaries, consensus statements, clinical recommendations and implications for research are presented in this article.